2014
DOI: 10.1530/jme-14-0220
|View full text |Cite
|
Sign up to set email alerts
|

PI3K/PTEN/Akt and TSC/mTOR signaling pathways, ovarian dysfunction, and infertility: an update

Abstract: Abnormalities in ovarian function, including defective oogenesis and folliculogenesis, represent a key female reproductive deficiency. Accumulating evidence in the literature has shown that the PI3K/PTEN/Akt and TSC/mTOR signaling pathways are critical regulators of ovarian function including quiescence, activation, and survival of primordial follicles, granulosa cell proliferation and differentiation, and meiotic maturation of oocytes. Dysregulation of these signaling pathways may contribute to infertility ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
115
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 180 publications
(132 citation statements)
references
References 114 publications
(92 reference statements)
4
115
0
2
Order By: Relevance
“…In this context, present findings represent the first evidence for the chemoprotective potential of natural antioxidant compounds against ovarian cytotoxicity and are consistent with previous results in the male gonad and other organs in mice (21,32,33). It is known that PFs are in a quiescent state by fine tuning of the PI3K/PTEN/Akt-FOXO3a pathway (17). Exposure to CPM disturbs this balance by up-regulating PI3K/PTEN/Akt axis, so leading to inactivation of FOXO3a and stimulation of follicle growth (16).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In this context, present findings represent the first evidence for the chemoprotective potential of natural antioxidant compounds against ovarian cytotoxicity and are consistent with previous results in the male gonad and other organs in mice (21,32,33). It is known that PFs are in a quiescent state by fine tuning of the PI3K/PTEN/Akt-FOXO3a pathway (17). Exposure to CPM disturbs this balance by up-regulating PI3K/PTEN/Akt axis, so leading to inactivation of FOXO3a and stimulation of follicle growth (16).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, it has been proposed that follicle "burnout" may be caused by increased follicle recruitment rather than PFs apoptosis. According to this model, CPM disrupts the regulatory mechanism underlying dormancy of PFs through inhibition of the transcription factor FOXO3a pathway, and stimulates follicle activation (16,17). Coadministration of AS101, an immunomodulator with chemopreventive effects in somatic tissues, promotes FOXO3a activity through downregulation of PI3K/PTEN/Akt pathway, thus reducing follicle recruitment and maintaining follicle reserve.…”
Section: Fertility Preservation In Cancer Patients: Attenuation Of Chmentioning
confidence: 99%
“…The elevated expression of BRAF and PRKAA2 genes via mTOR signaling pathway was seen in the short-DF hens. The mTOR signaling pathways are critical regulators of ovarian function including quiescence, activation, and survival of primordial follicles (PFs), granulosa cell (GC), proliferation and differentiation, and meiotic maturation of oocytes 42 . mTOR signaling pathway has been implicated in fertile egg production and female fertility in mice 43 , suggesting that BRAF and PRKAA2 genes via mTOR signaling pathways may be involved in regulating the DF trait.…”
Section: Discussionmentioning
confidence: 99%
“…24 Previous studies have shown that deterioration of the PI3K (phosphatidylinositol-4,5-bisphosphate 3-kinase)/PTEN (phosphatase and tensin homolog)/AKT (protein kinase B, PKB or AKT) pathway is able to impair follicular development, intrafollicular oocyte development, and ovulation and therefore is critical denominator of ovarian function. 25 Similarly, decreased presence of glucose transporter type 4 (Glut-4) on cell surface impairs glucose uptake and metabolism, thereby aggravating follicle growth. 20 Taking into account that older studies provided evidence that PCOS-derived granulosa cells are characterized by impaired insulin action, 26,27 the missing link between metabolic dysregulation and PCOS was the mechanism and the molecules by which the latter is mediated.…”
Section: Introductionmentioning
confidence: 99%